Distinct Dopamine Receptor Pathways Underlie the Temporal Sensitivity of Associative Learning - Handler, Annie; Graham, Thomas G W; Cohn, Raphael; Morantte, Ianessa; Siliciano, Andrew F; Zeng, Jianzhi; Li, Yulong; Ruta, Vanessa (Cell, 2019)
Animals rely on the relative timing of events in their environment to form and update predictive associations, but the molecular and circuit mechanisms for this temporal sensitivity remain incompletely understood. Here, we show that olfactory associations in Drosophila can be written and reversed on a trial-by-trial basis depending on the temporal relationship between an odor cue and dopaminergic reinforcement. Through the synchronous recording of neural activity and behavior, we show that reversals in learned odor attraction correlate with bidirectional neural plasticity in the mushroom body, the associative olfactory center of the fly. Two dopamine receptors, DopR1 and DopR2, contribute to this temporal sensitivity by coupling to distinct second messengers and directing either synaptic depression or potentiation. Our results reveal how dopamine-receptor signaling pathways can detect the order of events to instruct opposing forms of synaptic and behavioral plasticity, allowing animals to flexibly update their associations in a dynamic environment.